Autonomous WSNs node powered by a thermal energy harvester for temperature monitoring. Issue 1 (31st December 2023) - Zhang, Zhijuan; Ji, Xiaoming; Zhang, Qunjun; Hou, Liqun
Abstract : An autonomous wireless sensor networks (WSNs) node powered by a thermal energy harvester with MPPT is proposed in this paper for temperature monitoring. Two commercial TEG modules are used to build up the thermoelectric collector, while an energy management circuit with a DC/DC converter is employed to boost the TEG output voltage. The harvested energy is stored in a supercapacitor. The feasibility of the presented self-powered WSNs node is verified by a series of experiments with various node sleep periods and temperature differences across the thermoelectric generator (Δ T TEG ). The results show that the proposed thermal energy harvester can work at its maximum power point and autonomously power a commercial WSN node when Δ T TEG is above 13.3°C and node sleep period is not less than 1.5 s. In addition, the designed self-powered WSNs node can monitor the temperature of industrial devices successfully.